Gene Kloss An American Printmaker, a Raisonne. Volume 1 - Kloss, Gene frey50 (De Teves Pub Taos, New Mexico, 2009)
Collection of prints produced by Gene Kloss.
Keywords: Kloss, Gene -- 1903-1996; Southwest Art